Deconstructing the myth of the nonaggressive female: A feminist analysis - White, Jacquelyn W. (1994)
One of the most pervasive and undisputed gender stereotypes is that men are more aggressive than women. However, this stereotype has, until recently, led researchers to conclude that women are nonaggressive and, therefore, to ignore the topic of female aggression as a distinct phenomenon. The basis of the myth, factors supporting its maintenance, and theories of female aggression are examined. A feminist reinterpretation of aggression that views women's and men's aggressive behavior within social structural arrangements that create and sustain differential power relations is presented